A SEMIOTIC ANALYSIS OF KASKUS EMOTICONS (A Case Study of Kaskus Emoticons in the Lounge Forum at Kaskus the Largest Indonesian Community) - Ade Irma Junida, - (2011)
Kaskus (online forum) emoticons have been used widely in cyber, whether in Kaskus forum or blogs and other Instant Messengers (IMs). The use of emoticons in the forum is believed to be the latest way in communication among members. Dealing with this issue, this study entitled "A SEMIOTIC ANALYSIS OF KASKUS EMOTICONS (A Case Study of Kaskus Emoticons in the Lounge Forum at Kaskus the Largest Indonesian Community)" is aimed at analyzing the significance of Kaskus emoticons in the Lounge forum at the site since the use of the emoticons as a way to interact. The data were 28 Kaskus emoticons which were taken from five threads selected in the related forum. The study used a qualitative descriptive approach framed in semiotic analysis, particularly Roland Barthes' orders of signification to examine the significance of each emoticon. The findings reveal that the significance of those Kaskus emoticons was found based on their characteristics such as names, colors and emotions which have meaning and function as a way to communicate, particularly in the online forum. Kaskus emoticons serve as a means of (visual) communication between users to emphasize the statement in online communication. Moreover, it also portrays mood of the users which meant to show their thoughts. In short, the emoticons are created for covering complex function in online communication, especially Kaskus emoticons in Kaskus forum.